Influence of law and Order Situation upon University Sports, A Comparative Study of Public and Private Sector Universities of Khyber Pukhtunkhwa (KP) Pakistan - Syed Zia-Ul-Islam, Jalil-Ur-Rehman Baloch, Salahuddin Khan (JSSH, 2023)
The main objective of the study is to examine the existence and effect of law and order situation influencing sports participation among student athletes both in public and private sector universities of Khyber Pakhtunkhwa, Pakistan. All forms of terrorism like target killing, bomb blast, cracker attack etc. have been observed in Pakistan since 70s. Due to crude terrorist attacks in Pakistani institutions, people avoid any type of gathering oftenly. In recent years, many of the educational institutions are destroyed and remained closed due to serious threat of terrorists attack. Furthermore lack of security measures, a major concern for authorities also hindered against smooth conduction of various Extra and co-curricular activities in the educational institutions of Pakistan. Five main hypotheses were formulated to the requisite objectives of the study. Male and female athletes and director sports of both public and private sector universities were selected as population. The study was descriptive in nature and quantitative method was used. A proportionate random sampling technique was used for the selection of sample. The selected size of sample was 702 as whole (671 athletes and 31 director sports). A self-developed questionnaire was used containing of ten statements for the purpose of data collection. The content validity, pilot testing and reliability of the selfdeveloped questionnaire were also performed. For analyses of the data chi-square, sample linear regression, and t-test were applied as statistical tool with the help SPSS. According to participants law and order situation concern in both type of university as factor and natively affects sports participation among the athletes of both type of universities in KP, Pakistan. Furthermore, No significance difference was found between the response of athlete and director sports and male female athletes regarding the effect of law and order situation both type of universities in KP, Pakistan. Although more effect of law and order situation was found in private sector universities as compare to public sector universities.